ANALISIS PELAYANAN PENANGGULANGAN BENCANA KEBAKARAN OLEH PEMADAM KEBAKARAN PEMERINTAH (STUDI KASUS KOTA PONTIANAK) - hendayana s.stp (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2019)
Disasters are events that can occur anytime and anywhere, as well as fire disasters. Along with the frequent occurrence of fire disasters, it is necessary to provide effective, fast response services for fire disasters. Fires occur due to many factors. To reduce losses, it is necessary to improve services to fire services from the government which is one of the minimum services of the government. Analysis is a thinking activity to describe a whole as a component so that it can recognize the signs of components, their relationships with each other and their respective functions in an integrated whole. Service analysis is here to measure fire service levels in Pontianak City. This research is a descriptive qualitative research Measurement of service quality by using 5 (five) dimensions with several indicators of each dimension of Tangible, Reliabelity, Responsiviness, Assurance, Emphaty. Based on the results of research conducted stating that the fire disaster management service carried out by the Pontianak City Fire Department was not optimal This is because there are still problems faced by the Pontianak City Fire Department where firefighting organizations are not yet independent, lack of facilities and infrastructure, lack of resources humans, lack of fire stations, less attention to the apparatus regarding the safety guarantee of fire services especially.